A Commentary on Parent–Child Cognitive Learning Interaction Research: What Have We Learned from Two Decades of Research? - Harris, Yvette R.; Almutairi, Seham (Frontiers in Psychology, 2016)
The role of family influences on preschool and school age cognitive development has received considerable empirical attention from cognitive developmental psychology researchers in the last few decades. As a result of the interest, investigators have focused their attention on developing coding/observational systems to capture the interactions occurring between mothers and their young children. This paper reviews a select body of research on parent child cognitive learning interactions with the goal of determining how the researchers have operationalized the behaviors that occur within learning interactions. The paper concludes with a discussion of the suggestions on next steps for conducting parent child cognitive learning interaction research in the future.